The specificity of anti-carbamylated protein antibodies for rheumatoid arthritis in a setting of early arthritis. Issue 1 (December 2015) - Shi, Jing; van Steenbergen, Hanna; van Nies, Jessica; Levarht, E.; Huizinga, Tom; van der Helm-van Mil, Annette; Toes, René; Trouw, Leendert
Abstract Introduction Anti-carbamylated protein (anti-CarP) antibodies have been described in rheumatoid arthritis (RA) and arthralgia patients at risk of developing RA. To what extent these autoantibodies are specific for RA is unknown. Therefore, we investigated the diagnostic performance of the presence of anti-CarP antibodies for RA in a setting of early arthritis. Methods Anti-CarP antibodies were detected using carbamylated fetal calf serum as substrate. Anti-CCP2 antibodies were measured using enzyme-linked immunosorbent assay and immunoglobulin M (IgM) rheumatoid factor (RF) as part of routine care. Sera were derived from patients in the Leiden Early Arthritis Clinic cohort obtained at inclusion. Test characteristics were determined using the fulfillment of the 2010 RA criteria after 1 year as outcome. Results In total 2086 early arthritis patients were studied regarding the presence of anti-CarP antibodies. We observed that the sensitivity and specificity of the presence of anti-CarP antibodies for RA were 44 % and 89 %, respectively. As a reference, sensitivity and specificity of the presence of anti-CCP2 antibodies were 54 % and 96 %, respectively, and of IgM-RF 59 % and 91 %. Patients harboring anti-CarP antibodies not classified as RA were mainly diagnosed with undifferentiated arthritis and less frequently reactive arthritis and psoriatic arthritis. Conclusion Anti-CarP antibodies are predominantly present in RA but can also be detected in other forms of arthritis.